Preventing early learning failure - Sornson, Robert (Association for Supervision and Curriculum Development, 2001)
Each year thousands of young children come to school without good early learning experiences and are unprepared for school learning activities. Others have experienced physical or emotional setbacks that make learning difficult and frustrating. In Preventing Early Learning Failure, expert educators describe practices that can help children find success in school.